Evaluasi Efektivitas Penggunaan Anggaran Modal pada Koperasi Konsumen Syariah An-Nisa - Dzakirah, Nadiva; Ika Prajawati, Maretha (Jurnal EMT KITA, 2024)
This research aims to determine capital management and evaluate the effectiveness of using the capital budget. In this research, the research location was carried out at the An-Nisa Sharia Consumer Cooperative, Batu City. The research subjects were cooperative administrators who served as chairman. The method used is a descriptive qualitative method. Data collection techniques are used in interviews, observation, and documentation. The research results show that the condition of cooperatives in capital management and evaluation of effectiveness in using the capital budget from the previous year to the present is in very good condition. The existence of monthly, quarterly, semester and annual reports makes it more optimal for monitoring and reporting the condition of the cooperative.